Numerical study on a heat transfer model in a Lagrangian fluid dynamics simulation. (December 2016) - Takabatake, Kazuya; Sun, Xiaosong; Sakai, Mikio; Pavlidis, Dimitrios; Xiang, Jiansheng; Pain, Christopher C.
Graphical Abstract: Highlights: Heat flux could not be set in heat transfer simulation in the existing MPS method. Innovative heat transfer model was developed in the MPS method. A heat flux model was developed using divergence operator in the MPS method. Sign distance function could be introduced into the heat transfer simulation. Adequacy of the heat transfer model was shown through verification tests. Abstract: Phenomena related to phase change heat transfer are often encountered in engineering. These phenomena are regarded to be complex, since not only phase transition from solid to liquid occurs but also movement of fluid interface has to be taken into consideration. Detailed numerical modeling of these complex systems is essential to better understand them and optimize industrial designs. Lagrangian methods are promising for simulating such complex systems. The Moving Particle Semi-implicit (MPS) method, which is one of the Lagrangian methods, is employed here to simulate the free surface fluid flows involving heat transfer and phase change. On the other hand, the existing MPS method could not apply Neumann boundary condition such as heat flux in the heat transfer simulations. This is because the surface direction could not be readily defined on the surface of the spherical fluid particles in the MPS method. Hence, prescribing the heat fluxes becomes problematic in the existing MPS method. To solve this problem, a new heat flux model is developed, where the divergence operator is applied in the heat transfer simulation. Simple verification tests are performed to demonstrate the heat flux model, where the calculation results are compared against analytically derived solutions. In addition, application of the signed distance function is also investigated in the heat transfer simulation for arbitrary shaped boundary. In simple verification tests, the computation results are shown to agree well with the analytical solutions. Consequently, adequacy of the novel heat transfer model developed here is shown in the Lagrangian fluid dynamics simulation.